PENGARUH PEMBERIAN BIOCHAR TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN STEK LADA PADA LAPISAN TANAH SUBSOIL ULTISOL - Setiawan, Beny; Rosmalinda, Rosmalinda; Choirul Jannah, Wafiq (Journal of Agro Plantation (JAP), 2022)
Oil palm empty fruit bunch (TKKS) biochar has the potential to increase the availability of nutrients needed by plants, namely N, P, K, Ca and Mg, which aims to increase growth on pepper cuttings (Piper nigrum L) with subsoil ultisol as a medium. This study aims to determine the best composition of oil palm empty fruit bunch biochar for the growth of pepper cuttings. This research has been carried out from May to August 2022 on Jl. Brigjem Katamso No.02, Sukaharja, Delta Pawan District, Ketapang Regency, West Kalimantan. This study used a non-factorial Completely Randomized Design (CRD) with 5 treatments and 4 replications. Each treatment consisted of 3 plants so that 60 experimental units were obtained. Parameters observed included shoot height (cm), number of leaves (strands), shoot diameter (cm), shoot dry weight (grams), and root dry weight (grams). Based on analysis of variance, it was shown that giving biochar of oil palm empty fruit bunches with a composition of 15% biochar of oil palm empty bunches (150 g) + 80% ultisol subsoil (850 g) on ​​the growth of pepper cuttings had a significant effect on the parameters of plant height, number of leaves, diameter shoots, root volume, soil pH, and plant dry weight.